2020
DOI: 10.1038/s41419-020-03150-0
|View full text |Cite
|
Sign up to set email alerts
|

The HIF1α/HIF2α-miR210-3p network regulates glioblastoma cell proliferation, dedifferentiation and chemoresistance through EGF under hypoxic conditions

Abstract: Hypoxia-inducible factor 1α (HIF1α) promotes the malignant progression of glioblastoma under hypoxic conditions, leading to a poor prognosis for patients with glioblastoma; however, none of the therapies targeting HIF1α in glioblastoma have successfully eradicated the tumour. Therefore, we focused on the reason and found that treatments targeting HIF1α and HIF2α simultaneously increased tumour volume, but the combination of HIF1α/HIF2α-targeted therapies with temozolomide (TMZ) reduced tumourigenesis and signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 41 publications
(58 reference statements)
0
32
0
Order By: Relevance
“…In recent years, many studies have explored undifferentiated thyroid cancer at pre-transcription, transcription, and translation levels, revealing that a considerable number of undifferentiated cancers develop from dedifferentiation of DTC. Studies have shown that dedifferentiation of colorectal cancer is closely related to TGF-β, Wnt, and Hedgehog signaling pathways ( 35 ), while dedifferentiation of glioblastoma is closely related to hypoxia ( 36 ). Our previous studies have also shown that metabolic pathways play an important role in dedifferentiation of thyroid cancer ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many studies have explored undifferentiated thyroid cancer at pre-transcription, transcription, and translation levels, revealing that a considerable number of undifferentiated cancers develop from dedifferentiation of DTC. Studies have shown that dedifferentiation of colorectal cancer is closely related to TGF-β, Wnt, and Hedgehog signaling pathways ( 35 ), while dedifferentiation of glioblastoma is closely related to hypoxia ( 36 ). Our previous studies have also shown that metabolic pathways play an important role in dedifferentiation of thyroid cancer ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, also specific miRNAs associated with HIF-1α up-regulation are involved in chemoresistance. For instance, the HIF-1α/mir-210 axis determines resistance to temozolomide in glioblastoma by increasing the cell proliferation and the acquisition of a stemness phenotype [ 134 ]. In keeping with these results, mir-210 is considered a biomarker predictive of chemoresistance in patients with metastatic breast cancer [ 135 ].…”
Section: Hypoxia and Altered Upr: Two Partners In Crime Of Chemoresismentioning
confidence: 99%
“…Hypoxiainducible factor-1 is an oxygen-sensitive heterodimeric transcription factor composed of two subunits: α and β [217][218][219]. It was reported that chemoresistance is associated with a high level of HIF-1α expression in many cancer types including ovarian cancer, hepatocellular carcinoma, glioblastoma, and colorectal cancer [220][221][222][223]. Moreover, HIF-1α can trigger more than 60 genes involved in tumor growth, metastasis, cellular metabolism, the reduction of apoptosis, and poor prognosis [224,225].…”
Section: Hypoxia-inducible Factormentioning
confidence: 99%